2013
DOI: 10.1037/a0030592
|View full text |Cite
|
Sign up to set email alerts
|

Social influence online: The impact of social validation and likability on compliance.

Abstract: Text-based communication via the Internet has provided new opportunities to study social influence and persuasion. Specifically, Guadagno and Cialdini (2005) contend that the effectiveness of social influence attempts have yet to be thoroughly investigated online. To test Guadagno and Cialdini's contention, the present study examined whether the social influence principles of likability and social validation impacted individuals' willingness to comply with a request when the setting is online. Results revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 35 publications
(55 reference statements)
0
31
0
1
Order By: Relevance
“…A number of these can be linked to patterns of online behaviour (Guadagno & Cialdini, 2005), and demonstrate potential vulnerabilities that might be manipulated by fraudsters trying to deceptively gain the trust of users online for personal gain. Social proof, which provides insight on how to act in a given situation based on the behaviour of others and a desire to be liked, has been show to influence compliance online (Guadagno, Muscanell, Rice, & Roberts, 2013). Although compliance suggests only a surface-level change in behaviour, rather than a permanent attitude change (Turner, 1991), this is enough to have severe consequences for a user if they divulge security-related information as a result.…”
Section: Psychology Of Persuasionmentioning
confidence: 99%
“…A number of these can be linked to patterns of online behaviour (Guadagno & Cialdini, 2005), and demonstrate potential vulnerabilities that might be manipulated by fraudsters trying to deceptively gain the trust of users online for personal gain. Social proof, which provides insight on how to act in a given situation based on the behaviour of others and a desire to be liked, has been show to influence compliance online (Guadagno, Muscanell, Rice, & Roberts, 2013). Although compliance suggests only a surface-level change in behaviour, rather than a permanent attitude change (Turner, 1991), this is enough to have severe consequences for a user if they divulge security-related information as a result.…”
Section: Psychology Of Persuasionmentioning
confidence: 99%
“…Because the Internet offers so much information, individuals can experience cognitive overload and may be more likely to rely on heuristics such as social influence principles, as opposed to thinking effortfully. Some research has already shown that individuals routinely rely on heuristic cues when judging information and making decisions online (Guadagno & Cialdini, 2005;Guadagno, Muscanell, Rice, & Roberts, 2013;Metzger, Flanagin, & Medders, 2010). Additionally, individuals often multitask online which also increases cognitive load and decreases effortful thinking (Srivastava, 2013).…”
Section: Social Influence: Weapons Misusedmentioning
confidence: 99%
“…Highlighting the importance of social norms, the principle of social validation suggests that individuals seek social evidence that their own attitudes and behaviors are appropriate. Thus, when others appear to be similar in their beliefs and actions, people view their own attitudes and beliefs as being appropriate (e.g., Guadagno, Muscanell, Rice, & Roberts, 2013).…”
Section: Social Experience Of Flowmentioning
confidence: 99%